Nutritional Assessment of the Adolescents in the Northern State of Sudan - Khair Ahmed, Nur Mohammed; Onsa, Zeinab Osman (Pakistan Journal of Nutrition, 2014)
An investigation of the adolescents nutritional status in the Northern State was carried in urban and rural areas. 515 household chosen, populated by 1929 subjects. Adolescents aged (10<20 years) constituting 20.8% were selected from the households. Information on socioeconomic status, anthropometric measurements (BMI-for age), food habits and intake was collected by means of a questionnaire. Prevalence of under weight was a problem among adolescents in the state; which was highest in Albakri (28.6%), similar in Dongla and Marawi, lowest in Karima (16.9%). It was highest among males (29.4%) compared with (17.5%) among females. The gender difference was significant (p<0.021). The strongest predictor of under weight among adolescents was the household energy intake which contributed to about 77% of the variability, then came rural residency. Wheat was the staple food consumed mainly as gurasa. Meat as beef/mutton was used in small amounts to prepare the traditional meat/vegetable stew Mean energy intake was 1734 kcal/day, highest in Karima lowest in Albakri. Location differences were significant (p<0.004) but no urban/rural differences. Protein intake was adequate in 69.5% of the households, animal protein contributed 21.6% to total protein, highest in Karima and lowest in Albakri. Fat intake was inadequate in 83.9% of the households and carbohydrates were in excess in 62.5%. Albakri had the worst food intake because 74.0% of its households lived below the poverty line. The nutritional situation in the State needs further investigation particularly underweight among the adolescents.